Technical and Economic Evaluation of Pinavia Interchange in Comparison with Roundabout Intersection by AIMSUN - Kamran Rahimov; Alireza Motamadnia; Sadegh Samadi (Salehan Institute of Higher Education, 2016)
Interchanges that are investigated in this research are roundabout interchange and pinavia interchange that are simulated in AIMSUN software using traffic data. The parameters that are considered for each interchange are traffic volume, pollutant emissions, fuel consumption, travel time, delay time ,construction cost, repair and maintenance cost, travel time cost , fuel consumption cost and safety , so that in technical evaluation traffic volume, pollutant emissions, fuel consumption, travel time, delay time are compared by using two independent sample t – test that are used for comparing of two group of data and It is assumed that the variances are equal . Then In economic evaluation construction cost, repair and maintenance cost, travel time cost , fuel consumption cost and safety are converted into cost by using axis produce way that based on this supposal that storage in exchange for an hour of travel time, increase an hour of production opportunities and construction cost, repair and maintenance cost calculated by executive plans and Related Regulations and finally each parameter is weighted by AHP and obtain the universal (total) cost. Finally due to the total cost of the resulting it can be seen that for twenty-year period pinavia interchange in compare with roundabout interchange has 49% more efficient.